Nonlinear dynamic behavior of a long temperature-dependent FGM hollow cylinder subjected to thermal shocking - Dai Hong-Liang; Rao Yan-Ni (Science and Engineering of Composite Materials, 2014)
In this paper, the nonlinear dynamic behavior of a long hollow cylinder consisting of temperature-dependent functionally graded material (FGM) subjected to thermal shocking is investigated. Material parameters of the FGM hollow cylinder, except the Poisson’s ratio, are assumed to be graded continuously through the thickness according to the power law expressions, and they are assumed to be temperature dependent. The governing equation of the motion of the FGM hollow cylinder is obtained based on the plane-stain theory and together with the governing equation of the transient heat transfer problem is solved by the finite difference method, Newmark method, and iterative method. Numerical examples are carried out in which the Si3N4-SUS304 FGM hollow cylinders are considered, and some valuable dynamic thermoelastic characteristics of the FGM hollow cylinder subjected to symmetric or asymmetric thermal shocking are revealed.